Control Strategy For Wind Energy And Hybrid Generating Systems Based On The Concept Of Power Electronics (International Journal of Engineering and Computer Science, 2017)
The global electrical energy consumption is still rising and there is a steady demand to increase the power capacity. Deregulation of energy has lowered the investment in larger power plants, which means the need for new electrical power sources may be increased in the near future. In general, this paper discusses role of modern power electronics in small size wind energy and hybrid generating systems. A new and simple control method for maximum power tracking by employing a step-up dc-dc boost converter in a variable speed wind turbine system, using permanent magnet machine as its generator, is introduced. Output voltage of the generator is connected to a fixed dc-link voltage through a three-phase diode rectifier and the dc-dc boost converter. A maximum power-tracking algorithm calculates the reference speed, corresponds to maximum output power of the turbine, as the control signal for the dc-dc converter. This paper also proposes a hybrid energy system consisting of a wind turbine, a photovoltaic source, and a fuel cell unit designed to supply continuous power to the load. A simple and economic control with dc-dc converter is used for maximum power extraction from the wind turbine and photovoltaic array. Due to the intermittent nature of both the wind and photovoltaic energy sources, a fuel cell unit is added to the system for the purpose of ensuring continuous power flow.